The Effect of Lee's Strategy on the Acquisition of Arabic Grammar among Middle School Students - Hammadi, Hassan (Al-Adab Journal, 2023)
The current study aims to identify the Effect of Lee's Strategy on the Acquisition of Arabic Grammar among Middle School Students. To fulfill this goal, the researcher adopted an experimental design with partial control, including a specific test. The researcher intentionally chose “Sahl Bin Suhail Secondary School” which is affiliated with Baghdad Al-Rusafa /Third District. The number of the second-year intermediate classes in this school was two classes. The researcher randomly chose two groups: the experimental group that consists of 37 students who studied Arabic grammar using Lee’s strategy, and the other group consists of 38 students who studied Arabic grammar using the traditional method. After identifying the scientific material which is going to be used in the experiment, the researcher formulated the behavioral objectives whose total number, at the end of the experiment, became 60. The researcher prepared the teaching plans, and examples of them were presented to the experts.The researcher drafted the items of his test, and he presented them to the experts to choose what was appropriate for his research to represent the research tool. Accordingly, the researcher prepared a test to measure the acquisition of Arabic grammar, consisting of 25 items, in three questions (i.e., multiple choices, representation with useful sentences, and true and false), distributed among the six levels of Bloom’s Cognitive Taxonomy. After applying the experiment that lasted a full semester, the researcher applied the tool on the research sample by using several statistical methods, including a test for two independent samples analysis of variance. Finally, the study resulted in the following: the students of the experimental group outperformed the students of the second group in acquiring the Arabic grammar, and the differences were statistically significant between the students of the two groups.Among the most important conclusions drawn by the researcher are:Lee’s strategy is privileged over the traditional method in increasing the acquisition of Arabic grammar among second-year intermediate students.The effectiveness of teaching increases with Lee’s strategy when it comes to the subjects that have hierarchical structures of information, including Arabic grammar.In light of these results, recommendations can be made, including:Adopting Lee’s strategy in teaching Arabic grammar in order to reorganize the learned material with what exists in the learners’ previous cognitive structure.The need to train male and female Arabic grammar teachers on Lee’s strategy and include them in in-service training courses.The researcher suggested a number of proposals, including:Apply this study on other educational levels.Use this study for the purpose of demonstrating the effect of its independent variable according to the gender variable.